Implementation of Inquiry Method in Christian Education: Forming Highly Competitive Students Based on Critical Thinking - Barasa, Tiurma (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Critical thinking is needed by every student in solving problems, including finding problem-solving strategies. This study examines the implementation of inquiry methods in Christian religious education in forming critical thinking. Students are positioned as active learning subjects to create their learning experience independently and create critical thinking. Critical thinking is an effort to frame considerations from various points of view, understanding, interpretation, assumptions, and decision-making from relevant information. This study used a quantitative approach with instruments in the form of tests. The respondents were students of IAKN Tarutung, with a sample of 100 students. The data was analyzed with the paired sample t-test and processed with the help of SPSS 25.0 software. The analysis results showed a significance value of 0.000, or < 0.05, meaning a significant difference exists between the pre-test and post-test results. Thus, educators can implement inquiry methods in Christian education learning to form students who have high competitiveness.